Pengaruh Pelatihan dan Motivasi Terhadap Kinerja Karyawan dengan Kompetensi Sebagai Variabel Intervening Pada PT. Sisir Katarindo Kabupaten Bekasi - Yani Suryani; Christina Ekawati (Syntax Idea)
Increasing employee performance is an implication of adequate employee capabilities so that they are able to support the implementation of their duties and responsibilities professionally. This research aims to determine the effect of training and motivation on employee performance through competency as an intervening variable at PT. Sisir Katarindo, Bekasi Regency. The research used a quantitative approach; data was obtained through questionnaires distributed to all PT employees. Sisir Katarindo, which has 50 employees. The number of samples in this study was 50, or the same as the population, and the sampling technique was total sampling. Data analysis uses path analysis. The variables used in this research are the independent (exogenous) variables Training (X1) and Motivation (X2), the dependent (endogenous) variable Employee Performance (Y), and the intervening variable Competence (Z).The research results with Î± = 0.05 show that there is a significant positive influence of training on employee performance (P-values 0.00, T-statistic 6.324). The magnitude of the influence of training on employee performance is in the high category (f-square 0.918). There is a significant positive influence of motivation on employee performance (P-value 0.029, T-statistic 2.189). The magnitude of the influence of motivation on performance is in the medium category (f-square, 0.184). Competency does not have a significant effect on employee performance (P-value 0.525, T-statistic 0.620). There is a significant positive effect of training on competence (P-values 0.001, T-statistics 3.322). The magnitude of the effect of training on competence is moderate (f-square 0.3). Motivation has no significant effect on competence (P-values 0.531 and T-statistic 0.627); training has no significant effect on employee performance through competence as an intervening variable (P-values 0.555 and T-statistic 0.59); and motivation has no significant effect on employee performance through competence as an intervening variable (P-values 0.786 and T-statistic 0.271).